Pulau Sebira Dalam Karya Batik Dengan Pewarna Alami Kayu Bakau (Program Studi Pendidikan Seni Rupa FBS UNJ, 2021)
Sebira Island is one of the islands located in the northernmost part of the Thousand Islands, DKI Jakarta Province which has a lot of natural beauty that can be an inspiration in a work of art. This study aims to implement visual objects that characterize the environment of Sebira Island into a batik motif by exploring stylization and shape deformation so that the formation of Batik Sebiran. In addition, this study also uses Red Mangrove (Rhizopora stylose) as a dye in batik. This research method uses qualitative methods by conducting exploratory trials on motifs, natural dyes, and designs in designing Sebiran Batik. This type of research and creation research uses Research-led Practice, where in the research and creation of Sebiran batik works, research was carried out first to get results from concept exploration which then the results of the research were implemented into a work. The results obtained are Sebiran batik with five different designs with motifs inspired by the environment of Sebiran Island. Each design provides a philosophy of various motifs that are arranged into batik works. The unique environment of Sebira Island becomes a motif in written batik works by visualizing the environment that is characteristic of Sebira Island such as Hawksbill turtles, lighthouses from the Dutch colonial era, pidada trees, barongko, which are typical foods of the Bugis tribe, boats and selar fish.